In vitro assessment of the toxicity of gold nanoparticles - Vetten, Melissa Anne (My University, 2019)
The hazard identification of gold nanoparticles forms an essential part of their risk assessment; however, the test methodologies used should be appropriate and applicable to ensure reliable results. In this study, various in vitro testing methodologies used for hazard identification were investigated for their applicability in the testing of gold nanoparticles. Preferable assays were identified, in particular, the use of label-free methodologies, such as the cell impedance based xCELLigence and the CytoViva HSI systems, were found to be ideal in order to avoid optical interference of the nanoparticles with the testing methodology. The recommended tests were then implemented to investigate the effect of size, surface charge and different functional groups in the bronchial epithelial cell line BEAS-2B. Two citrate stabilized gold nanoparticles of 14 nm and 20 nm in diameter were tested. Moreover, the 14 nm polyethylene glycol-liganded AuNPs with either hydroxyl, carboxyl, biotin, nitrilotriacetic acid, or azide negatively charged functional groups, and the positively charged 14 nm polyethylene glycol-liganded AuNP with amine functional group were investigated. The characterization of the physicochemical characteristics and sterility of these nanoparticles were performed prior to the assessment of their toxicity, intracellular uptake and localization, and the mechanism of uptake. The gold nanoparticles tested were not toxic or genotoxic to the BEAS-2B cells, regardless of cellular internalisation. These cellular effects were not influenced by their size or surface charge. On the other hand, surface functionalization influenced uptake, which was shown to be through a caveolin-mediated endocytosis pathway followed by accumulation within vesicles and in the cytosol. However, additional work needs to be conducted to establish the link between different functional groups and their role in endocytosis and subsequent localization and toxicity. In conclusion, the possibility exists for the interference of nanoparticles with in vitro assays and this should be tested prior to their implementation. However, most importantly, the physicochemical characterization of nanoparticles is of utmost importance, which should precede the hazard identification of nanomaterials using these in vitro assays. These in turn, will allow the establishment of the relationship between these characteristics and any observed toxicity, which will aid not only the risk assessment of nanomaterials but also in the establishment of predictive models in the toxicity of newly synthesised nanomaterials.
A Thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, 2019
Keywords: Particles; Nanoparticles--therapeutic use; Biopharmaceutics--methods; Nanostructured materials